Direct aesthetic restoration of black triangles in anterior teeth with a bio clear matrix: case series - Han Zheng; Fuhua Zhang; An-na Wang; Huang Tao; Yuhang Cao; Zhang, Lei (Journal of the Pakistan Medical Association, 2025)
The black triangle, a V-shaped gap between anterior teeth, affects both dental aesthetics and self-esteem. It can negatively impact dental aesthetics and patients’ self-esteem. This study presents a series of cases in which a novel Bioclear matrix system was used for the direct aesthetic restoration of black triangles in anterior teeth. Three patients were treated at Hefei Stomatological Hospital, China, in 2023. The procedure involved cleaning, etching, applying a bonding agent, using a bioclear matrix to inject the resin composite, and light curing. Twelve-month follow-ups revealed intact restorations with no significant issues. Using the bioclear matrix provides a non-invasive and predictable method for correcting black triangles. Keywords: Bioclear matrix, black triangle, direct aesthetic restoration.